Rwanda : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
The government of Rwanda has recognized that economic development in most areas would have to be the responsibility of the private sector (particularly since military and civil service employment would be reduced), but that the public sector could still have a role in promoting economic equality by providing a social safety net, most importantly with a solvent social security system. Before the conflict in 1994, the private sector has accounted for only about 50 percent of employment in the formal sector, excluding the civil service.